Assembled milk protein nano-architectures as potential nanovehicles for nutraceuticals - Tang, Chuan-he (Advances in colloid and interface science, 2021)
Nanoencapsulation of hydrophobic nutraceuticals with food ingredients has become one of topical research subjects in food science and pharmaceutical fields. To fabricate food protein-based nano-architectures as nanovehicles is one of effective strategies or approaches to improve water solubility, stability, bioavailability and bioactivities of poorly soluble or hydrophobic nutraceuticals. Milk proteins or their components exhibit a great potential to assemble or co-assemble with other components into a variety of nano-architectures (e.g., nano-micelles, nanocomplexes, nanogels, or nanoparticles) as potential nanovehicles for encapsulation and delivery of nutraceuticals. This article provides a comprehensive review about the state-of-art knowledge in utilizing milk proteins to assemble or co-assemble into a variety of nano-architectures as promising encapsulation and delivery nano-systems for hydrophobic nutraceuticals. First, a brief summary about composition, structure and physicochemical properties of milk proteins, especially caseins (or casein micelles) and whey proteins, is presented. Then, the disassembly and reassembly behavior of caseins or whey proteins into nano-architectures is critically reviewed. For caseins, casein micelles can be dissociated and further re-associated into novel micelles, through pH- or high hydrostatic pressure-mediated disassembly and reassembly strategy, or can be directly formed from caseinates through a reassembly process. In contrast, the assembly of whey protein into nano-architectures usually needs a structural unfolding and subsequent aggregation process, which can be induced by heating, enzymatic hydrolysis, high hydrostatic pressure and ethanol treatments. Third, the co-assembly of milk proteins with other components into nano-architectures is also summarized. Last, the potential and effectiveness of assembled milk protein nano-architectures, including reassembled casein micelles, thermally induced whey protein nano-aggregates, α-lactalbumin nanotubes or nanospheres, co-assembled milk protein-polysaccharide nanocomplexes or nanoparticles, as nanovehicles for nutraceuticals (especially those hydrophobic) are comprehensively reviewed. Due to the fact that milk proteins are an important part of diets for human nutrition and health, the review is of crucial importance not only for the development of novel milk protein-based functional foods enriched with hydrophobic nutraceuticals, but also for providing the newest knowledge in the utilization of food protein assembly behavior in the nanoencapsulation of nutraceuticals. [Display omitted] •Milk proteins are excellent starting materials to build nutraceutical nano-architectures.•Casein micelles are natural nanovehicles for nutraceuticals.•Caseins can be utilized to form nanovehicles through different disassembly and reassembly strategies.•Whey proteins can be assembled into versatile nano-architectures through different strategies.•Milk protein based nano-architectures as nanovehicles for nutraceuticals are revieweds.